Análisis del impacto en la gestión tecnológica en tiempos de covid-19 en las pequeñas y medianas empresas en la ciudad de Babahoyo. - Domínguez Cerruffo, Jonathan Daniel (2022)
In the present work it is proposed to analyze the technological management in the SMEs of the city of Babahoyo in times of pandemic, since, due to the health emergency, many companies were forced to close their doors in person and adapted to the use of the internet and technology to offer their services and at the same time to have direct contact with their suppliers. The analysis also emphasizes the impact of technology on SMEs in times of pandemic and how it affects their development, since many have always been immersed in traditional ways, carrying out all their processes and records manually, running the risk of losing valuable information from companies, customers and/or suppliers to the point of ignoring technology to opt for a change for their own benefit and thus leave traditional methods behind and bet on digital and technological methods.